PELATIHAN PEMBUATAN POSTER YANG MENARIK MENGGUNAKAN CANVA PADA SISWA SMP NEGERI 1 KEDUNGBANTENG - Kaffqa Tegar Gayuh Pamungkas; Desmonda Varel Robel Salim; Rafi Nail Praditama; Valen Yuda Perwira; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the current digital era, visual communication skills have become an essential capability for junior high school students to support both academic tasks and creative activities. However, the ease of access to digital design tools such as Canva has not been fully balanced with a basic understanding of proper graphic design principles. This research aims to equip students at SMP Negeri 1 Kedungbanteng with a correct visual literacy foundation through socialization activities and sharing sessions. The research method applied is descriptive qualitative, involving 20 students selected purposively by the school. Data collection techniques were carried out through participatory observation during activities, interactive discussions in Q&A sessions, and documentation of the learning process. The focus of the material presented includes the 60-30-10 color proportion principle, visual hierarchy, font pairing selection, and the application of grid and margin systems. The research results indicate that a direct socialization approach is effective in increasing students' enthusiasm and technical understanding. There was a transformation in the participants' mindset, from initially arranging visual elements randomly to becoming more structured and proportional. The implications of this activity emphasize that education regarding essential design rules is crucial to help students produce independent visual works that are informative, organized, and attractive.